2000
DOI: 10.1097/00007632-200008150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thoracolumbosacral Orthosis on Spinal Deformities, Trunk Asymmetry, and Frontal Lower Rib Cage in Adolescent Idiopathic Scoliosis

Abstract: Thoracolumbosacral orthosis program maintained the measured roentgenographic parameters at the prebrace levels in progressive adolescent idiopathic scoliosis, but it had no effect on the droop of the seven lower ribs. The TLSO treatment stopped progression of scoliosis and reduced the number of patients requiring surgery. Thus, it changed the natural history of scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…Especially for the thoracic curves, the Cobb angles and the translation angles were reduced in the coronal and sagittal plane. Therefore, the brace Our results are confirmed by other studies that have showed that brace treatment had a lordotic effect on the thoracic kyphosis [6,7]. At this time, MR animation is a new procedure with a potential for use in monitoring the brace effect in scoliosis.…”
Section: Discussionsupporting
confidence: 84%
“…Especially for the thoracic curves, the Cobb angles and the translation angles were reduced in the coronal and sagittal plane. Therefore, the brace Our results are confirmed by other studies that have showed that brace treatment had a lordotic effect on the thoracic kyphosis [6,7]. At this time, MR animation is a new procedure with a potential for use in monitoring the brace effect in scoliosis.…”
Section: Discussionsupporting
confidence: 84%
“…The effect of bracing in altering the natural history of progressive adolescent idiopathic scoliosis seems nowadays to be almost generally accepted [12,25]. However, bracing has a quantifiable impact on several aspects on adolescent and family functioning [13,30].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Since first introduced, braces have usually been recommended to be worn on a 20 -23 hours a day basis, 3,[5][6][7][8][9] and the effectiveness of bracing has depended on this full-time regimen. 3,4,8 However, compliance with the full-time regimen is limited and difficult to measure.…”
mentioning
confidence: 99%